Human activity selectively affects a dynamic defensive mutualism - Bailey Franco; Cooper Kinne; Savannah Licciardello; Hali Muir; Holland J. Smith; Sean O'Fallon; Daniel T. Blumstein (Animal Behaviour, 2024)

Working memory gating in obesity: Insights from a case-control fMRI study - Nadine Herzog; Hendrik Hartmann; Lieneke K. Janssen; Maria Waltmann; Sean J. Fallon; Lorenz Deserno; Annette Horstmann (Appetite, 2024)

Self-reported intake of high-fat and high-sugar diet is not associated with cognitive stability and flexibility in healthy men - Hendrik Hartmann; Lieneke K. Janssen; Nadine Herzog; Filip Morys; Daniel Fängström; Sean J. Fallon; Annette Horstmann (Appetite, 2023)

The benefits of being big and diverse: early colony survival in harvester ants - Blaine J. Cole; Dayne Jordan; Montrel LaCour‐Roy; Sean O’Fallon; Logan Manaker; John J. Ternest; Megan Askew; Daniel Garey; Diane C. Wiernasz (Ecology, 2022)
In sessile organisms such as plants and benthic invertebrates, founding propagules typically suffer extremely high rates of mortality due to both extrinsic and intrinsic factors. Many social insect species share similarities with these groups, but factors influencing early colony survival are relatively unstudied. We used a field experiment to measure the importance of environmental quality relative to intrinsic colony properties in the harvester ant, Pogonomyrmex occidentalis , by monitoring the survival of 584 experimental colonies. We measured survival of transplanted colonies over four months in each of three years (2014–2016) at a site in western Colorado. Colony survival was primarily determined by colony features. Multiple mating by the queen and larger colony size at the time of transplant increased survival, but queen size, maternal lineage and the composition of plant species in the vicinity of the colony did not. Food supplementation increased survival significantly when natural food was scarce, but was not consistently beneficial, in contrast to predictions. Our results emphasize the general importance of rapid growth and early attainment of large size in the survival of sessile species. However, attributes specific to ants that are a consequence of their sociality also strongly affected survival. Colonies with multiply‐mated queens were more likely to survive over a wide range of circumstances, highlighting the importance of this trait even at the early stages of colony life.

Catecholaminergic modulation of trust decisions - Cătălina E. Rățală; Sean J. Fallon; Marieke. E. van der Schaaf; Niels ter Huurne; Roshan Cools; Alan G. Sanfey (Psychopharmacology, 2019)